The Heart Physiology in Fertile Female and The Heart Pathophysiology in Post Menopausal Female. The Contribution of Molecular Biology, Maintaining Cardiac Hemodinamy and Electrophysiology - Samuel Sclarosky (International Physiology Journal, 2024)
Maintaining Cardiac Hemodinamy and Electrophysiology
Keywords: Fertile Female